2013
DOI: 10.1007/s00467-013-2496-6
|View full text |Cite
|
Sign up to set email alerts
|

CUL3 gene analysis enables early intervention for pediatric pseudohypoaldosteronism type II in infancy

Abstract: Since chronic acidosis and hypertension associated with PHA-II can result in delayed growth and development in pediatric patients, genetic analysis to detect the CUL3 mutation and to enable intervention early in the disease course would be beneficial for infants with suspected PHA-II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…Interestingly, although FHHt patients with mutations in CUL3, KLHL3 or WNK present the same clinical symptoms, those with mutations in CUL3 have a more severe phenotype, evident in terms of both an earlier age-of-onset and the degree of hypertension and electrolyte disturbance reported [15, 84, 85]. So far, all the reported FHHt CUL3 mutations show the deletion of exon 9 in the CUL3 mRNA which results in the loss of amino acid residues 403–459 in the protein.…”
Section: Cul3–klhl3 As Upstream Regulators Of Wnk Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although FHHt patients with mutations in CUL3, KLHL3 or WNK present the same clinical symptoms, those with mutations in CUL3 have a more severe phenotype, evident in terms of both an earlier age-of-onset and the degree of hypertension and electrolyte disturbance reported [15, 84, 85]. So far, all the reported FHHt CUL3 mutations show the deletion of exon 9 in the CUL3 mRNA which results in the loss of amino acid residues 403–459 in the protein.…”
Section: Cul3–klhl3 As Upstream Regulators Of Wnk Kinasesmentioning
confidence: 99%
“…So far, all the reported FHHt CUL3 mutations show the deletion of exon 9 in the CUL3 mRNA which results in the loss of amino acid residues 403–459 in the protein. These mutations are heterozygous and autosomal dominant [15, 84, 85]. Two different mouse models of CUL3 have been reported, to date.…”
Section: Cul3–klhl3 As Upstream Regulators Of Wnk Kinasesmentioning
confidence: 99%
“…47 However, faced with only mild hyperkalemia, the only certain way to diagnose PHAII is to do genetic studies. Thus, Osawa et al 48 in 2013 found a mutant cullin3 (CUL3; see below) in a 1-yearold boy with hypertension and mild hyperkalemia, which sealed the diagnosis of PHAII.…”
Section: Hypertensionmentioning
confidence: 98%
“…Increased expression of CUL3 (Cullin 3) in the caudate basal ganglia was associated with increased risk of AN in our study (OR=1.07). Dysregulation of CUL3 is associated with pseudohypoaldosteronism 77 , a disorder characterized by sodium imbalance in the body and often presenting with low body weight. Mutations in CUL3 are associated with schizophrenia 78 , autism 79 and non-response to anti-depressants 80 .…”
Section: Discussionmentioning
confidence: 99%